变速传动轴承内齿圈齿廓方程的分析 - 杨坤玉; 潘存云 (Jixie chuandong)
According to the nature of parallel curves, a new method to derive the tooth profile equation of gear ring and surge wheel of the shifting drive bearing is presented in this paper. And some calculating formulas are provided, which can fit to circle surge wheel. This method is much simpler than conventionally used enveloping method, and gives a basis for processing the tooth profile of the internal gear of the shifting drive bearing.